Tunable THz filter based on random access metamaterial with liquid metal droplets - Chia, Elbert E. M. (2014)
Here we report a tunable THz filter based on random access metamaterial with liquid metal droplet, which is tuned through electrical bias controlled electrowetting effects. The random access metamaterial consists of 80 × 80 micro droplets, which are self-assembled in micro holes array due to lotus effect. The simulation results indicate resonant dip frequency shift of about 0.01THz induced by changing of the droplets shape via electrowetting effect and about 0.6 THz frequency shift when the droplets are connected in different forms. The random access metamaterial is realized through simple fabrication processes and can be tuned easily, which has potential application on tunable filters, tunable beam steering and flat lens.